Impact of an education and multilevel social comparison–based intervention bundle on use of routine blood tests in hospitalised patients at an academic tertiary care hospital: a controlled pre-intervention post-intervention study. Issue 10 (10th February 2020) - Ambasta, Anshula; Ma, Irene Wai Yan; Woo, Stephen; Lonergan, Kevin; Mackay, Elizabeth; Williamson, Tyler
Abstract : Background: Repetitive inpatient laboratory testing contributes to waste in healthcare. We evaluated an intervention bundle combining education and multilevel social comparison feedback to safely reduce repetitive use of inpatient routine laboratory tests. Methods: This non-randomised controlled pre-intervention post-intervention study was conducted in four adult hospitals from October 2016 to March 2018. In the medical teaching unit (MTU) of the intervention site, learners received education and aggregate social comparison feedback and attending internists received individual comparison feedback on routine laboratory test utilisation. MTUs of the remaining three sites served as control units. Number and cost of routine laboratory tests ordered per patient-day before and after the intervention was compared with the control units, adjusting for patient factors. Safety endpoints included number of critically abnormal laboratory test results, number of stat laboratory test orders, patient length of stay, transfer rate to the ICU, and 30-day readmission and mortality. Results: A total of 14 000 patients were included. Pre-intervention and post-intervention groups were similar in age, sex, Charlson Comorbidity Index and length of stay. From the pre-intervention period to the post-intervention period, significantly fewer routine laboratory tests were ordered at the intervention MTU (incidence rate ratio=0.89; 95% CI 0.79 to 1.00; p=0.048) with associated costs savings of C68 877 (p=0.020) as compared with the control sites. The variability in the ordering pattern of internists at the intervention site also decreased post-intervention. No worsening was noted in the safety endpoints between the pre-intervention and post-intervention period at the intervention unit compared with the controls. Conclusions: Combination of education and multilevel social comparison feedback significantly and safely led to cost savings through reduced use of routine laboratory tests in hospitalised patients.